2018
DOI: 10.1186/s40425-018-0393-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic immune-related adverse events associated with adjuvant ipilimumab: report of two cases

Abstract: BackgroundPD-1 and CTLA-4 inhibitors are associated with several adverse events including a spectrum of immune-related adverse effects (irAEs). Neurologic irAEs are uncommon occurrences with varied presentations. We describe two separate cases of ipilimumab associated meningoencephalomyelitis and demyelinating polyneuropathy with unusual presentations.Case presentationTwo melanoma patients were treated with ipilimumab in the adjuvant setting. The first patient developed a meningoencephalitis following 3 doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 46 publications
0
44
0
1
Order By: Relevance
“…only reporting the most severe or obvious cases), or over-reporting (reporting cases without a firmly established diagnosis). This study does, however, complement other detailed descriptions of these clinical syndromes [6][7][8][9][10][11]. Third, we are unable to definitively determine the incidence of each event using Vigibase, although other studies have reported incidence of neurologic toxicities in the range of 1-5% [7,8].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…only reporting the most severe or obvious cases), or over-reporting (reporting cases without a firmly established diagnosis). This study does, however, complement other detailed descriptions of these clinical syndromes [6][7][8][9][10][11]. Third, we are unable to definitively determine the incidence of each event using Vigibase, although other studies have reported incidence of neurologic toxicities in the range of 1-5% [7,8].…”
Section: Discussionmentioning
confidence: 73%
“…Neurologic toxicities have emerged as clinically relevant complications of ICI. Case series have reported limited numbers of autoimmune-like, inflammatory events including encephalitis, aseptic meningitis, myasthenia gravis, and Guillain-Barre Syndrome which may occur, in aggregate, in 1-5% of treated patients [6][7][8][9][10][11]. However, a systematic analysis of the timing, spectrum, clinical associations, and outcomes of these uncommon events has not been performed in a large number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Immunotherapy with immune checkpoint inhibitors (inhibitory monoclonal antibodies against the cytotoxic T-lymphocyte antigen-4 (CTLA-4) and programmed death 1 (PD-1/ PDL1) and targeted therapy (Vemurafenib and nivolumab) acted as a certain efficiency on metastatic melanoma; unfortunately, these immune-based therapies are not fully responsive in some advanced stage melanoma. 5,6 In this regard, it is desirable to adopt an efficient therapeutic strategy to overcome the shortage in successful treatment of metastatic melanoma based on immune checkpoint inhibitors and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although ipilimumab was approved for the adjuvant treatment of melanoma patients by the FDA (but not by the EMA) based on a placebo-controlled phase III trial reporting superior recurrence-free and overall rates, its use was internationally disputed given the relatively high frequency of serious immune-related adverse events in patients receiving treatment with ipilimumab [33][34][35]. In Europe, nivolumab was the first checkpoint inhibitor approved for adjuvant treatment of melanoma patients, based on results of the CheckMate 238 study reported in 2017 [36].…”
Section: Peri-operative Usementioning
confidence: 99%